Labor Rights in the Era of the Gig Economy: Regulatory Challenges and Legal Protection in Indonesia - Melti Wulandari; Susanto; Edi Sofwan (Journal of Legal and Cultural Analytics, 2026)
The rapid growth of the gig economy has transformed labor relations in Indonesia through digital platform-based work arrangements. While gig work offers flexibility and employment opportunities, it also creates legal uncertainty regarding workers’ status and limits access to fundamental labor protections. This study aims to analyze the legal status of gig workers within Indonesia’s labor law system and identify regulatory challenges in ensuring fair legal protection. The research employs a normative legal method using statutory, conceptual, and comparative approaches supported by primary, secondary, and tertiary legal materials. The findings reveal that existing labor regulations remain oriented toward conventional employment relationships and fail to accommodate platform-mediated work. As a result, gig workers occupy a legal grey area, restricting their access to minimum wage protection, social security, and safeguards against unilateral termination. The study recommends regulatory reform recognizing new employment relationships and establishing a specific legal framework for gig workers.